Enhancing student engagement through gamification in teaching telling-time expressions in elementary EFL classrooms - Setyaningsih Rachmania; Bahruddin Mustafa; Sri Setyarini (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2026)
Student engagement is a crucial factor in successful English as a Foreign Language (EFL) learning, particularly at the elementary school level, where learners often struggle to understand abstract language concepts. One topic that frequently challenges young learners is telling time in English, which requires the integration of linguistic and numerical understanding. This study aims to examine how gamification enhances student engagement and learning outcomes in teaching telling-time expressions in an elementary EFL classroom. This study employed a qualitative case study approach involving 47 elementary school students aged 7–9 years at a public school in Bandung, Indonesia. Data were collected through classroom observation, semi-structured interviews, and document analysis of students’ formative assessments. The data were analyzed descriptively to identify patterns of engagement and learning achievement during gamified classroom activities. The findings reveal that gamified learning activities significantly increased students’ behavioral, emotional, and cognitive engagement. Observation results showed that 87% of students actively participated in the game-based activities, while 85% demonstrated enthusiasm and positive attitudes toward the learning process. Participation records further indicated that most students were consistently involved in classroom activities. In addition, formative assessment results showed that 77% of students achieved good or excellent scores in identifying and writing English time expressions. Interview findings also suggest that students perceived gamified learning as enjoyable and motivating. These findings demonstrate that non-digital gamification strategies can create a more interactive learning environment and effectively support young learners’ understanding of telling-time expressions in EFL contexts.